Behavioural and fitness effects of translocation to a novel environment: Whole‐lake experiments in two aquatic top predators - Monk, Christopher T.; Chéret, Bernard; Czapla, Philipp; Hühn, Daniel; Klefoth, Thomas; Eschbach, Erik; Hagemann, Robert; Arlinghaus, Robert; Börger, Luca (The Journal of animal ecology, 2020)
Translocation into a novel environment through common fisheries management practices, such as fish stocking, provides opportunities to study behavioural and fitness impacts of translocations at realistic ecological scales. The process of stocking, as well as the unfamiliarity with novel ecological conditions and the interactions with resident fish may affect translocated individuals, leading to alterations of behaviours and causing fitness impacts. Our objectives were to investigate how aquatic top predators behaviourally establish themselves and compete with resident individuals following introduction in a novel lake environment and to investigate the resulting fitness consequences. Using high‐resolution acoustic telemetry, we conducted whole‐lake experiments and compared the activity, activity‐space size and fate of translocated and resident individuals in two model top predators, the northern pike Esox lucius (n = 160) and European catfish Silurus glanis (n = 33). Additionally, we compared the reproductive success of translocated and resident northern pike. The experiment was conducted with large (adult) individuals of different origins, resilient to predation, but subject to agonistic interactions and competition with resident fish. Over a period of several months, the translocated catfish exhibited consistently larger activity‐space sizes than resident catfish, but did not differ from residents in activity and survival. The pike from one of the two translocated origins we tested also showed elevated space‐use, and both translocated origins revealed higher mortality rates than their resident conspecifics, indicating maladjustment to their novel environment. When non‐resident pike reproduced, they overwhelmingly produced hybrid offspring with resident fish, indicating that introductions fostered gene flow of non‐native genes. Our study indicates that fish introductions result in behavioural and fitness impacts even in large‐bodied top predators that experience low levels of natural predation risk. Adult top predators of two species (pike and catfish) translocated to a novel environment show persistant behavioural differences compared to resident conspecifics over a period of several months post‐translocation. Fish introductions result in behavioural and fitness impacts even in large‐bodied top predators that suffer from low levels of natural predation risk.